LUGAR DA BIOLOGIA EDUCACIONAL NA FORMAÇÃO DE PEDAGOGOS NA FACULDADE DE FILOSOFIA, CIÊNCIAS E LETRAS DE UNIÃO DA VITÓRIA (1960-1989) - Metelski, Michele (2013)
This dissertation has the objective of discussing tha place of Educational Biology in Pedagogy course in Faculdade de Filosofia, Ciências e Letras de União da Vitória College (FAFI), in the limited context between the years of 1960 and 1989. This analysis leans in Pierre Bordieu concepts, mainly in the field and habitus categories for learning the formats in the area of pedagogy and teachers formation apropriating the Educational Biology knowhow. The analytical route of this problem has privileged two fronts, firstly the discussion has followed from general to particular, seeking the analysis structure relationally. Due to this option, narrative has been organized taking the history of higher education in Brazil, mainly by the history of FAFI to remodel some aspects of creation. To reach the specific point of our discussion was necessary to understand how this institution has been settled in Union ad Victoria and who were the idealization agents. In another front this research has privileged an approach to the Educational Biology trajectory, associating to the medical speech and the attempt of making a field for teachers formation in Brazil. Seeking to explain the real place of this area of knowledge subject in the training formation of the pedagogue. This second discussion was the main concern of the dissertation, because it explains the answer to the formulated problem. These terms, the textual plot of the second chapter has came from the general to the particular as well, seeking to stablish an analytic web between the national formulations mainly Almeida Junior, Ary Lex and the organization of knowledge in the Pedagogy course in FAFI. This analytical structure allows explain the following statements: 1) FAFI constituition in a context of expansion of elementary and secondary school, as well as the interiorization of the higher education in Paraná state; 2) FAFI was born with the responsability to form teachers to teach in normal schools/education institutes and secondary schools; 3) FAFI was created as a political strategy of Paraná state integration and to build a regional identity; 4) In the 1960´s there was a mismatch among discussion waged in a national, hygine precepts were not mentioned; 5)The teaching was only about the fundamental Educational Biology, learning some gaps in the formation of the ones that graduated during this period; 6) The genetic approach was extensive, occupying the place of the application part that was the main importance to the teachers formation that would prepare normal school teachers. 7) The instability of the Educational Biology in the 1960´s is observed because contents were minimum and its nomenclature varied among General Biology, Educational Biology and Biological elements of education and sometimes its contents were in the interior of the didatic discipline; 8) In the 1970´s Biology occupied a more solid place, complete and with it´s own characteristics, particularly with School Hygine introduction; 9) In the 1980´s the Educational Biology was divided between School Hygine and Biology enphatizing the medical character to treat new deseases, especially AIDS; 10) In 1989´s, the Educacional Biology assumed a permanent condition in the Pedagogy course in FAFI.